2021
DOI: 10.1007/s10856-020-06478-3
|View full text |Cite
|
Sign up to set email alerts
|

Sol–gel based synthesis and biological properties of zinc integrated nano bioglass ceramics for bone tissue regeneration

Abstract: Bone is a flexible and electro active tissue that is vulnerable to various traumatic injuries. The self-healing of damaged bone tissue towards reconstruction is limited due to the lack of proper niche compliances. Nevertheless, the classical grafting techniques like autograft/allograft for bone repair pose challenges like bacterial infections and donor-site morbidity with unsatisfactory outcomes. The use of appropriate biomaterial with osteogenic potential can meet these challenges. In this regard, bioactive g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 50 publications
(67 reference statements)
1
14
0
Order By: Relevance
“…The essential role played by Zn 2+ ions in cell behavior, modulating cell signaling, has attracted increasing attention in the biomedical field, particularly for regenerative-medicine applications and wound healing [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. In addition, Zn +2 presents antimicrobial activity, both as an antibacterial and antifungal agent [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The essential role played by Zn 2+ ions in cell behavior, modulating cell signaling, has attracted increasing attention in the biomedical field, particularly for regenerative-medicine applications and wound healing [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. In addition, Zn +2 presents antimicrobial activity, both as an antibacterial and antifungal agent [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of bone injuries is still a challenge [ 36 ] for regenerative medicine, and, thus, there is a need to manufacture biomaterials and improve treatment protocols that enable bone replacement quickly and safely [ 37 ], overcoming the limitations of conventional techniques of autograft and allograft, which can lead to unwanted infections and donor site morbidity [ 38 ]. However, some factors must be considered in the formulation of these products, such as their biocompatibility, surface type and porosity, mechanical strength, physical-chemical and biological composition, and the three-dimensional arrangement that allows osteoconduction [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Paramita et al found that integration of zinc ions could promote the osteoconductive properties as compared to the pure nano-bioglass ceramics particles. 51 Westhauser et al reported that doping of ionic dissolution products in 5 Zn-MBG nanoparticles not only upregulated the expression of OPN and OCN but also significantly increased extracellular matrix calcification and collagen production. 52 Khader and Arinzeh demonstrated that addition of 1 and 2.5 wt % ZnO nanoparticles increased the gene expression of chondrogenic differentiation markers such as SOX-9, aggrecan, chondroadherin, and collagen type II, while the addition of 5 and 10 wt % ZnO nanoparticles promoted osteogenic differentiation, as evident by enhanced ALP activity, collagen production, and the expression of osteogenic markers.…”
Section: Effects Of Zinc Ions In Bone Tissuementioning
confidence: 99%
“…Zinc ions are also known to facilitate osteogenesis. Paramita et al found that integration of zinc ions could promote the osteoconductive properties as compared to the pure nanobioglass ceramics particles . Westhauser et al reported that doping of ionic dissolution products in 5 Zn-MBG nanoparticles not only upregulated the expression of OPN and OCN but also significantly increased extracellular matrix calcification and collagen production .…”
Section: Effects Of Zinc Ions In Bone Tissue Engineeringmentioning
confidence: 99%